Sistem Kemanan Data Menggunakan Algoritma Kriptografi Blowfish Pada Aplikasi Chatting - Nursakti (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Lamappapoleonro, 2018)
The way message delivery may no longer have to use paper as a message medium, now we can use many applications to exchange messages such as email, chat, and so forth. in real terms if the message on email or chat is very important and must be kept confidential the prevention is to apply security system on the chat to prevent from unauthorized people such as sniffing. Blowfish cryptography is an encryption method similar to DES (Data Encryption Standard) (DES-like cipher) and created by Bruce Schneier devoted to large microposesors (32 bits upwards with large data cache). in this study raised classical cryptography as the basis of understanding of cryptographic algorithms and applied its use through the computer program of message security with encryption method using blowfish cryptography algorithm